KONSEP PEMBAHARUAN PEMIDANAAN DALAM RANCANGAN KUHP - Darmadi, A.A Ngurah Oka Yudistira (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013), 2013)
Criminal law reform in principle is an attempt to conduct a review and reestablishment of law in accordance with the common values of socio-political, sociophilosophic, and cultural values of the people of Indonesia. Renewal of the Criminal Code criminal law angle can be done in two ways. First, the partial renewal, by replacing part after part of the codification of the criminal law. Second, with the renewal of a general nature, thorough renewal by replacing total codification of the criminal law. underlying purpose of a criminal law reform in Indonesia, including to determine the political purposes to which a bill is nationally Indonesian State covers all aspects of society with keanegaragaman nation based on Pancasila. The draft penal code reform set an another solution in addition to the imposition of imprisonment and he organized an action against the perpetrators of criminal deprivation of liberty.
Keywords: Renewal; sanctions; Criminalization and draft the Code of Criminal